2015
DOI: 10.1371/journal.pone.0128984
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Autophagy Genes Are Associated with Paget Disease of Bone

Abstract: Paget disease of bone (PDB) is a focal bone disorder affecting the skeleton segmentally. The main alteration resides in osteoclasts that increase in size, number and activity. Many osteoclasts have cytoplasmic inclusions that have been associated with protein aggregates, increasing the evidences of a possible deregulation of autophagy in the development of the PDB. Autophagy starts with encapsulation of the target into a double-membrane-bound structure called an “autophagosome.” It has been reported that at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
0
26
2
9
Order By: Relevance
“…29 In contrast, in another study of 238 patients with paget disease of bone (PDB) and 264 sex-matched controls, Usategui-Martin et al found that genotype frequencies did not significantly differ between PDB patients and healthy subjects. 45 In the present study, we observed that ATG2B rs17784271 variant G allele was associated with a poor LRFS and PFS, but we did not find an association of the variant genotypes with risk of severe RP and OS in patients with NSCLC, suggesting that the ATGB2 rs17784271 variant G allele may play a role in the LRF and PFS of NSCLC after definitive radiotherapy.…”
Section: Discussioncontrasting
confidence: 77%
“…29 In contrast, in another study of 238 patients with paget disease of bone (PDB) and 264 sex-matched controls, Usategui-Martin et al found that genotype frequencies did not significantly differ between PDB patients and healthy subjects. 45 In the present study, we observed that ATG2B rs17784271 variant G allele was associated with a poor LRFS and PFS, but we did not find an association of the variant genotypes with risk of severe RP and OS in patients with NSCLC, suggesting that the ATGB2 rs17784271 variant G allele may play a role in the LRF and PFS of NSCLC after definitive radiotherapy.…”
Section: Discussioncontrasting
confidence: 77%
“…In contrast, the C‐allele did not affect morbidity risk of this disease . Unlike our study, previous findings indicated that the GG genotype of this polymorphism increases morbidity of thyroid carcinoma and that the ATG5 G‐allele increases the risk of morbidity, whereas in the current study C‐allele improves the risk of morbidity of lung cancer. Others showed that the frequency distribution of genotypes in myeloma disease was not significantly different between patients and healthy controls .…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, it was shown that GG genotype of the intronic polymorphism rs2245214 can be a protective factor for NSCLC, which may be due to regulatory effects by this polymorphism on ATG5 function; future in-depth studies are warranted. In a study by Usatequi-Martin et al, 30 no significant relationship between genotype of the rs2245214 ATG5 gene polymorphism and risk of morbidity of Paget's disease was observed. This finding is different from ours, which may be due to a distinct disease nature of Paget's disease and lung cancer.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…El polimorfismo de ATG5 rs2245214 genera un cambio intrónico y ha sido previamente estudiado en enfermedades como la tuberculosis, el lupus eritematoso, la enfermedad ósea de Paget, el cáncer de tiroides no medular y el melanoma (145)(146)(147)(148). En nuestro estudio no hemos encontrado diferencias significativas entre los pacientes con SL, PAF, CCR esporádico y el grupo control.…”
Section: Análisis De Polimorfismos En Genes Relacionados Con La Autofunclassified